The firing cost implications of alternative severance pay designs - Donald O. Parsons (Institute for the Study of Labor (IZA), 2010)
Economists have concerns about the firing cost implications of mandated severance plans. Analysis reveals that predicted severance plan consequences depend critically on the precise structure of the plan. Whether governments mandate (i) severance insurance plans or (ii) severance savings plans is important; savings plans have no firing cost effects on employer layoff decisions. The firing cost implications of insurance plan are sensitive to the types of job separations that qualify a worker for benefits. Plans that pay benefits across all separations are functionally severance savings plans. The variety of plan types is illustrated using U.S. and international examples.
Keywords: J65; J41; J33; 330; Job displacement; worker turnover; severance pay; firing costs; Abfindung; Kündigung; Kosten; Sozialplan; Sparen; Versicherung; USA; Welt